Genesis 14: A Diaspora Novella? - Glissmann, Volker (2009)
The influence of the Babylonian golah on the redaction of the biblical material is widely attested. This article suggests that the redaction of Genesis 14 addresses specific diaspora concerns, and for this reason should be located within a diaspora setting. In light of this, Genesis 14 is examined in two ways. First, Meinhold’s characteristics of a diaspora novella are traced throughout the narrative of Genesis 14. Second, the argument for a specific diaspora redaction is enhanced through a reading of the text from a diaspora perspective. Overall, this article argues that the narrative in Genesis 14 can be classified as a diaspora novella.
Keywords: identity marker; Abram; Genesis 14; diaspora novella; Exile; Diaspora